Problem Posing Setting Kooperatif untuk Meningkatkan Kemampuan Menyelesaikan Masalah Matematika Siswa - Yuntawati, Yuntawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to describe the process of problem posing cooperative settings to improve the ability to solve math problems class VIII MTs Al Raisiyah Sekarbela. This study is a classroom action research (conducted in two cycles, each cycle consisting of planning, execution, observation and reflection) The research subjects are the students of grade VIII C MTs Al Raisiyah Sekarbela who need 23 students Data completion technique with test and non-test (observation, and interview) .The data analysis using qualitative descriptive analysis technique.The learning process of cooperative posing problem problem in this research is the teacher gives the picture of the situation and the students in groups answered the problem as well as finding the solution and raise new problem based on the problem given later presented the results to conduct a joint discussion in the classroom.The results showed that the problem of setting cooperative posing improves the ability to solve mathematical problems which is the result of student learning that students achieve mastery learning in the classical.Another result sho ws.